BUTIJA WEAVING CRAFTS IN TAOPA BARAT VILLAGE, PARIGI MOUTONG REGENCY, CENTRAL SULAWESI PROVINCE - Najmi, Nur; Mondong, Tonny Iskandar; Arrazaq, Naufal Raffi; Tasnur, Irvan (Satmata: Journal of Historical Education Studies, 2025)
Traditional weaving is a national cultural heritage with high historical, aesthetic, and economic value. Each region in Indonesia has its own unique weaving craft, including Butija Weaving, which originates from Taopa Barat Village, Parigi Moutong Regency, Central Sulawesi. However, the sustainability of Butija Weaving faces various challenges. Lack of interest from the younger generation, limited market access, and lack of support from the village government are the main obstacles to its development. This study aims to analyze the production process, challenges, and opportunities for the development of Butija Weaving in Taopa Barat Village, Parigi Moutong Regency, Central Sulawesi Province. This study used a descriptive qualitative approach, with data collected through observation, interviews, and literature review. The results show that the Butija Weaving craft business has significant economic and cultural potential despite facing limitations. Product marketing has reached areas outside the village, indicating promising economic opportunities. Further government support is needed in the form of capital, training, and market access to increase product competitiveness.